2011
DOI: 10.1088/0004-637x/737/2/89
|View full text |Cite
|
Sign up to set email alerts
|

Prelude to a Double Degenerate Merger: The Onset of Mass Transfer and Its Impact on Gravitational Waves and Surface Detonations

Abstract: We present the results of a systematic numerical study of the onset of mass transfer in double degenerate binary systems and its impact on the subsequent evolution. All investigated systems belong to the regime of direct impact, unstable mass transfer. In all of the investigated cases, even those considered unstable by conventional stability analysis, we find a long-lived mass transfer phase continuing for as many as several dozen orbital periods. This settles a recent debate sparked by a discrepancy between e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
283
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 174 publications
(298 citation statements)
references
References 51 publications
(83 reference statements)
11
283
1
Order By: Relevance
“…We also compare our results of M 0.9 0.6 +  and k M 100 1 - with those from the previous studies of Yoon et al (2007), Dan et al (2011), andZhu et al (2013). Since these studies have used similar resolutions (a few 10 5 SPH particles in all), they are suitable for comparison.…”
Section: Comparison With Previous Studiesmentioning
confidence: 57%
See 3 more Smart Citations
“…We also compare our results of M 0.9 0.6 +  and k M 100 1 - with those from the previous studies of Yoon et al (2007), Dan et al (2011), andZhu et al (2013). Since these studies have used similar resolutions (a few 10 5 SPH particles in all), they are suitable for comparison.…”
Section: Comparison With Previous Studiesmentioning
confidence: 57%
“…If the initial separation is smaller when the RLOF starts, the mass transfer tends to occur more violently and the secondary is completely disrupted within a few orbital periods (Dan et al 2011). As a result, accreted matter is more strongly shockheated and dynamic carbon burning easily occurs.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter case would result in a near-M Ch SN Ia event, with the same potential explosion mechanisms listed above. (2) Recent multi-dimensional hydrodynamical simulations have shown that an accretion disc need not form, and the resulting violent merger of the two WDs may lead to a detonation in the primary (Pakmor et al 2010(Pakmor et al , 2011(Pakmor et al , 2012Dan et al 2011;Raskin et al 2012). In this violent merger model, the explosion is essentially driven by a pure detonation of a nearly hydrostatic sub-M Ch WD.…”
Section: Introductionmentioning
confidence: 99%